2005
DOI: 10.1099/jmm.0.46058-0
|View full text |Cite
|
Sign up to set email alerts
|

16S rDNA PCR and denaturing gradient gel electrophoresis; a single generic test for detecting and differentiating Mycoplasma species

Abstract: Diagnosis of Mycoplasma infection is normally based on culture and serological tests, which can be time-consuming and laborious. A number of specific PCRs have been developed but to date there has not been a single generic test capable of detecting and differentiating mycoplasmas to a species level. This report describes the development of a new diagnostic test based on PCR of the 16S rRNA gene with Mycoplasma-specific primers and separation of the PCR product according to primary sequence using denaturing gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 15 publications
2
140
0
Order By: Relevance
“…method (McAuliffe et al, 2005) is a sensitive single generic test capable of detecting and differentiating mycoplasmas to the species level. By DGGE, the ibex isolate was observed to be a Mmc serovar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…method (McAuliffe et al, 2005) is a sensitive single generic test capable of detecting and differentiating mycoplasmas to the species level. By DGGE, the ibex isolate was observed to be a Mmc serovar.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Mycoplasma DNA was extracted as stated above for the PCR. The PCR and DGGE were performed as described by McAuliffe et al (2005).…”
Section: Polymerase Chain Reaction Denaturing Gradient Gel Electrophomentioning
confidence: 99%
See 1 more Smart Citation
“…The ISR sequences were identical, in accordance with the isolates' high phenotypic similarity. Furthermore, 16S rRNA gene sequence similarity was studied by means of denaturing gradient gel electrophoresis (McAuliffe et al, 2005), which suggested that the isolates' 16S rRNA gene sequences were also identical (data not shown).…”
mentioning
confidence: 99%
“…DGGE is a molecular approach to detect variation between sequences within a population, or even a community. Through this method, the amplified products of the genes of interest will be used in gel electrophoresis under constant heat by increasing concentration of denaturing agents (formamide or urea) (Muyzer et al, 1993;Walter et al, 2000;McAuliffe et al, 2005). Hydrogen bonds between base pairs will be broken by different concentrations of denaturing agents at a constant temperature.…”
Section: Snps Such As Denaturing Gradient Gel Electrophoresis (Dgge) mentioning
confidence: 99%